Um estudo de t?cnica de codifica??o cooperativa em canais com desvanecimento seletivo em frequ?ncia - Marins, Tiago Reis Rufino (2012)
This work presents an analysis of the performance of Reed Solomon in a cooperative communication system. This analysis is evaluated in flat, time-varying and frequency selective channels. The OFDM technique is employed in the transmission of user data and has the function of improving system performance in frequency-selective fading channels, providing methods that the base station can use for the channel estimation. The source user performance is measured in terms of the cooperation ratio and in terms of the percentage of the subcarriers of the user relay that are above a reception threshold.